The Rhetoric of Influence: Reflections from Diplomacy, Boardrooms, and Peacebuilding - Susan Laverick (Ukrainian Policymaker, 2025)
In an age of manipulated narratives and fractured public trust, ethical and persuasive rhetoric has become a critical necessity. Drawing on contemporary practitioner insight, this article explores how influence can be ethically forged across diplomatic, corporate, and peacebuilding contexts. Anchored in Aristotle’s rhetorical principles – logos, ethos, páthos – and the Sophist-derived concept of kairos, it draws on case studies from Geneva, Bosnia, a Southeast Asian diaspora, and Ukraine. The result is a methodology for crafting messages that shape perception, build trust, and drive change. Persuasion is not a luxury; it is a strategic imperative.